Pengembangan Model Pendugaan Kadar Hara Tanah Melalui Pengukuran Daya Hantar Listrik Tanah - Hasbi Mubarok Suud; M. Faiz Syuaib; I Wayan Astika (Jurnal Keteknikan Pertanian, 2015)
The key of precision farming is the right decision in terms of time, quality, quantity, and specific location in the farming activities. Soil electrical conductivity (EC) is a variable that is both practical and efficient to implement precision farming. Several methods of EC measurement for precision farming have been developed and applied in precision farming, but inaccuracy on the interpretation of measurement result frequently encountered due to complexity of soil conditions and various geospatial condition. This paper presents a study on EC interpretation by focusing on interaction between moisture content, soil density, and soil N, P, K ratio which affect soil EC measurement. Soil samples of various levels of water, compaction, and N, P, K ratio are measured using a soil box resistivity. The levels of moisture contents were devided into low moisture content that have moisture content less then 20% and high moisture content that have moisture content more than 20%, while the levels of soil compaction were devided into high density condition and low density condition. Regression equations for N, P, and K ratio prediction have been generated and the coefficient of determination (R2) were obtained ranging between 0.6 and 0.89 for low moisture content and